Attenuation of Detrimental Effects of Formaldehyde on Sperm Chromatin Quality and Rate of Apoptosis in Mice by Curcumin - Abbas Shahedi; Morteza Anvari; Aghdas Mirjalili; Majid Pourentezari (Journal of Kerman University of Medical Sciences, 2021)
Background: The present study aimed to evaluate the sperm chromatin quality and rate of apoptosis in formaldehyde (FA)-exposed mice and the possible protective effects of curcumin (Cur) on the fertility potential of spermatozoa.Methods: Twenty-four adult male NMRI mice were randomly divided into three groups: Group Ι (control), group ΙΙ (Sham) received Cur solvent (2 ml/day, intraperitoneal), group ΙΙΙ received FA (10 mg/kg, intraperitoneal), and group ΙV received FA+Cur (100 mg/kg, intraperitoneal). After 35 days, the spermatozoa from right cauda epididymis were analyzed using Chromomycin A3 (CMA3) and TUNEL staining.Result: Regarding CMA3 and TUNEL tests, the data revealed a significant increase (p <0.05) in control and sham groups compared to the FA and FA+Cur groups. There was also a significant decrease in CMA3 tests and apoptosis in FA+Cur group compared to FA group (p <0.05).Conclusion: Cur, as a potent antioxidant, can attenuate detrimental effects of FA on the chromatin quality and apoptosis in an experimental animal model.